The Contingent Effect of Management Practices. (24th July 2019) - Blader, Steven; Gartenberg, Claudine; Prat, Andrea
Abstract: This article investigates how the success of a management practice depends on the underlying values articulated by the management. A large U.S. transportation company is in the process of fitting its trucks with an electronic on-board recorder (EOBR) to provide drivers with information on their driving performance. The company also has commenced a multi-year initiative to remake its internal operations, the first phase of which focuses exclusively on changing values toward a greater emphasis on teamwork and empowerment. In this setting, a natural question is whether the optimal managerial practice consists of: (1) letting each driver know his or her individual performance only; or also (2) providing drivers with information about their performance with respect to other drivers. Using the EOBR-provided driver performance data, we randomize these practices across sites. The main result of our experiment is that (2) leads to better performance than (1) in a particular site if and only if the site has not yet received the values intervention, and worse performance if it has. The result is consistent with the presence of a conflict between competition-based managerial practices and a shift to a cooperation-based value system. More broadly, it highlights the role of intangible factors in determining the optimal set of managerial practices.